Effective ultrasonication process for better colloidal dispersion of nanofluid - Mahbubul, I.M.; Saidur, Rahman; Amalina, M.A.; Elcioglu, E.B.; Okutucu-Ozyurt, T. (Elsevier, 2015)
Improving dispersion stability of nanofluids through ultrasonication has been shown to be effective. Determining specific conditions of ultrasonication for a certain nanofluid is necessary. For this purpose, nanofluids of varying nanoparticle concentrations were prepared and studied to find out a suitable and rather mono-dispersed concentration (i.e., 0.5 vol., determined through transmission electron microscopy (TEM) analyses). This study aims to report applicable ultrasonication conditions for the dispersion of Al2O3 nanoparticles within H2O through the two-step production method. The prepared samples were ultrasonicated via an ultrasonic horn for 1-5 h at two different amplitudes (25 and 50). The microstructure, particle size distribution (PSD), and zeta potentials were analyzed to investigate the dispersion characteristics. Better particle dispersion, smaller aggregate sizes, and higher zeta potentials were observed at 3 and 5 h of ultrasonication duration for the 50 and 25 of sonicator power amplitudes, respectively. (C) 2015 Elsevier B.V. All rights reserved.